Skill Development – A Tool for Human Capital Formation: Exploring the Role of Skill Education in Human Capital Formation and Economic Growth (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Make in India is an initiative of the Government of India to support global, just as homegrown, organizations to make their items in India. It was dispatched by Prime Minister Narendra Modi on 25 September 2014. The achievement of this undertaking relies on the skilled human assets. Skill education is key for human capital formation. It is the essential duty of educational institutions to give skill education. The back rub Sikho huner bano honhar given by Honorable prime minister indicates the significance of skill education for youth.The essential target of this paper is to zero in on the employability of education. This examination is an endeavor to investigate the job of skill education in human capital formation and the job of higher educational institutes in providing itThis paper surveys the present status of education, skills development and considers the difficulties facing India's skills development framework. This article closes with the note that the skill education and training is required for formation of human capital just as for the accomplishment of make in India development. Most of youngsters have restricted admittance to education and training, and most find work in the informal area. Lately India has quickly extended the limit of educational institutions and enrolments, however dropout rates remain high, and educational attainment remains low. Hence India can't exploit its segment profit.